The Sound Detection for Hearing Impairment Education: A Qualitative Case Study on Auditory and Non-Verbal Communication in Deaf Children - Putri Kuswo Hana; Suci Rismawati; Wagino; Khofidotur Rofiah (GRAB KIDS: Journal of Special Education Need, 2026)
This research investigates how auditory and non-verbal communication methods affect the language development of a 9-year-old child with severe bilateral hearing loss. Adopting a qualitative, descriptive approach, the study focuses on the influence of techniques such as sound differentiation, articulation training, and non-verbal communication, including sign language, in enhancing the child’s linguistic abilities. The participant in this study, NNR, is enrolled in a Special Education Elementary School (SDLB) in Sidoarjo, East Java. Data was gathered through interviews with NNR's teacher and mother, as well as medical records and observation forms. The findings highlight that non-verbal communication methods, particularly sign language and visual aids, are vital for enabling hearing-impaired children to develop language skills. These techniques help bridge the gap caused by limited auditory input, allowing children to develop both expressive and receptive communication abilities. Additionally, the research emphasizes the essential role of parental involvement in reinforcing these skills outside the classroom. The collaboration between the teacher and parents helped establish a consistent learning environment, where NNR was able to apply classroom lessons to real-life situations. Despite these positive outcomes, the study also identifies several challenges in implementing the intervention. The diverse degrees of hearing loss and speech abilities among children require tailored approaches, as standardized methods are often insufficient. Inconsistent home practice, due to time limitations and the parents’ understanding of the necessary techniques, further complicated the intervention's effectiveness. Moreover, some children need supplementary medical and therapeutic support, such as speech therapy and hearing treatments, which are not always readily accessible. The research concludes that a comprehensive and individualized approach, incorporating educational methods, family involvement, and medical intervention, is critical to successfully supporting the language development of hearing-impaired children. This study emphasizes the need for a holistic strategy to address the unique needs of these children.